Gone with the wind - Mitchell, Margaret, 1900-1949.; Conroy, Pat. (New York : Pocket Books, 2008)
Willful and pampered Scarlett O'Hara's strength of character carries her thought the deprivations of the Civil War, but her infatuation with Ashley Wilkes keeps her from recognizing her true love until it is too late.
Originally published: 1936.
Adult.
Adult
Keywords: Women -- Georgia -- History -- 19th century -- Fiction; Historical fiction; War stories; Women -- Georgia -- History -- Fiction; Georgia -- History -- Civil War, 1861-1865 -- Fiction; Georgia -- History -- Fiction; United States -- History -- 1861-1865, Civil War -- Fiction; Historical fiction; War stories